(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Salinity fluctuations in estuaries can significantly impact marine organisms, leading to economic losses through mass mortalities of commercially important species. The effects of varying estuarine salinities on the survival, daily mortality, and growth of adult and juvenile hard clam Meretrix meretrix under controlled aquarium conditions were investigated. Adults (shell length 45 mm) and juveniles (shell length 30 mm) were collected from an 18 ppt estuarine habitat in Chowfaldondi, southeast Bangladesh, and exposed to six salinity levels (10, 15, 20, 25, 30, and 35 ppt) with three replications at ambient temperature. Adults were monitored for 51 days and juveniles for 23 days. Survival was significantly higher (≥80%) at 15–30 ppt for adults and 10–20 ppt for juveniles, with the lowest survival at 35 ppt. Analysis of co-variance showed that salinity had a greater effect on survival than the combined salinity*size model (p<0.05). While adult clams exhibited no mortality in first 15 days, juvenile mortality ( 10%) began on day two across all salinities with a dose-dependent mortality exceeding 50–80% in 25–35 ppt. Adults were more tolerant to high salinities while juveniles to low salinities. Shell length and width did not vary significantly across salinities, likely due to insufficient plankton in the supplied seawater. This study has implications for potential site selection for coastal clam aquaculture along the Bay of Bengal. The sudden changes and combined effects of multi-stressors on bivalves can be assessed for better understanding how near future climate change can impact bivalve fishery and blue economy. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 239-254